Formation of the top yield of purple echinacea depending on the “Biogor” microbiological fertilizer - O. Yu. Artemova; E. V. Sumina; S. V. Beletsky (Новые технологии, 2025)
Introduction. For the efficient cultivation of medicinal crops, including echinacea, in industrial production conditions, it is necessary to develop and improve adaptive agricultural technologies aimed at obtaining high yields of high-quality medicinal raw materials.   The goal of the research is to study the effect of different brands and doses of the Biogor microbiological fertilizer of the KM series on the growth, development of plants, and the yield of air-dry matter of purple echinacea in the soil and climatic conditions of the Belgorod region.   The Methods. Field studies were carried out on the experimental field of the Belgorod branch of the Federal State Budgetary Scientific Institution VILAR in 2022-20223. The field experiment was set up in accordance with the methodology for conducting field experiments with medicinal and essential oil crops (VILAR, 2023). The experimental design included a control and 11 experimental variants using two brands of the Biogor microbiological fertilizer - Development and Finish at doses of 1.0 and 2.0 l/ha, both separately and in different combinations.   The Results. The research showed that the highest yield of air-dry mass of purple coneflower was ensured by double application of the Biogor Development microbiological fertilizer at a dose of 2.0 l/ha in the 3-4 leaf phase and 1.0 l/ha in the 6-8 leaf phase in combination with the treatment of crops with Biogor Finish at doses of 1.0 and 2.0 l/ha in the budding phase before the first mowing. On average, over two years of research, the yield of purple coneflower grass by the sum of two cuttings in these experimental variants was 3.30 and 3.23 t/ha, respectively, which was 1.52 and 1.45 t/ha more than the control.   Conclusions. Thus, the studied brands and doses of the Biogor microbiological fertilizer of the KM series in the conditions of the Belgorod region contributed to the activation of growth processes in purple coneflower plants and an increase in its top yield.